Design of controller for a machine light intensity insolation - Martínez-Baquero, Javier Eduardo; Parrado-Sandoval, Elías; Morales-Suarez, Luis Enrique (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
This paper presents a design for a insolation machine controller used in curing processes. This development began conducting a thorough prior review to the actual insolation machine and the procedures to be carried out in the printing laboratory, in order to understand the process of curing, assessing the possibilities for improving the equipment in use. The proposed controller design is a PID, which was made with matlab simulation tools, giving priority to the exposure time in the process of curing which must be the same for any type of fabric or mesh frame. This will allow the insolation machine does not require to be operated by highly qualified and competent staff in this art.